P6_6 Interstellar Space Pirates: Design Decisions - Strachan-Deol, Jack; Knowles, Katie; Thompson, Laura; Kelly, Aidan (Physics Special Topics, 2021)
The authors present in the following paper an analysis of how the journey time of a typical pirate ship withmass 1.270×10^5kg travelling from Earth to Proxima Centauri, varies with solar sail area. Also presentedis the analysis of the journey time as a function of area-mass ratio to investigate whether there is a pointof diminishing returns. Lastly, a comparison between the journey duration profiles when using aluminium,silver or gold is presented, in which it is concluded that using silver would result in the shortest journeytime, albeit not by a large amount.